1998
DOI: 10.1088/0953-2048/11/3/012
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue behaviour at room temperature and its influence on superconducting properties at 4.2 K of multifilamentary composite wire

Abstract: Fatigue behaviour at room temperature and its influence on superconducting current and upper critical magnetic field at 4.2 k were studied using multifilamentary composite wire with a copper ratio of 1.55 and an overall diameter of 0.812 mm in which 241 filaments are embedded. The filament itself was not fractured by the fatigue when tested separately. In the composite, the fatigue cracks nucleated in the copper, which grew and caused the fracture of the filaments. When the maximum stress in the fatigue te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
12
0

Year Published

1999
1999
2003
2003

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 15 publications
9
12
0
Order By: Relevance
“…These results also demonstrate that the probe is suitable for studying the influence of fatigue on the transport properties of superconducting wires and tapes. Such studies are complementary to other investigations which address multiple cyclic loading ͑up to 10 7 cycles͒ at room temperature, prior to measurements at 4.2 K. [31][32][33]…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…These results also demonstrate that the probe is suitable for studying the influence of fatigue on the transport properties of superconducting wires and tapes. Such studies are complementary to other investigations which address multiple cyclic loading ͑up to 10 7 cycles͒ at room temperature, prior to measurements at 4.2 K. [31][32][33]…”
Section: Resultsmentioning
confidence: 86%
“…This property offers the additional possibility of using the probe to examine the effect of fatigue on the transport properties of wires and tapes. [31][32][33] These general considerations convinced us to choose CuBe alloy as the material for the spring. The spring can be machined first and subsequently precipitate hardened but particular precautions have to be taken during the heat treatment in order to maintain the shape of the spring.…”
Section: B Spring 1 Materials For the Spring Fabricationmentioning
confidence: 99%
“…As mechanical and electromagnetic stresses acting during fabrication and/or service of superconducting composite wires affect the superconductivity, it is necessary to clarify the mechanical behaviour and its relation to the superconductivity. Recently the present authors [1,2] have studied the static and fatigue behaviours at room temperature and their influences on critical current at 4.2 K of an Nb 3 Al composite wire which has been developed for wide engineering application owing to the high critical current densities at high magnetic field and high strain endurance and low strain sensitivity of the critical current [3][4][5][6][7][8][9]. Concerning the static behaviour at room temperature, it was found that (a) the scatter of tensile strength of the multifilamentary composite is very small in spite of the large scatter of strength of the Nb 3 Al filaments and (b) the strength of the composite wire has a very slight dependence on length, although the strength of the Nb 3 Al filaments decreases markedly with increasing length.…”
Section: Introductionmentioning
confidence: 89%
“…Concerning the fatigue behaviour at room temperature and its influence on critical current at 4.2 K, the following features have been observed [2]. (d) The Nb 3 Al filament itself is not fractured by fatigue when it is not embedded in copper, but is fractured when it is embedded owing to the propagation of the fatigue crack nucleated in the copper.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation